The Influence of Accounting Information Systems and Internal Control on the Effectiveness of Managerial Decision-Making in MSMEs - Bella Suci Novitri; Walla Astianty Putri; Joko Rianto; Muhammad Fikri (Indonesia Journal of Engineering and Education Technology (IJEET), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting economic growth, employment generation, and regional development. However, many MSMEs continue to experience limitations in producing accurate financial information and implementing effective internal control systems, thereby reducing the quality and timeliness of managerial decision-making. This study aims to examine the influence of Accounting Information Systems (AIS) and Internal Control on the effectiveness of managerial decision-making in MSMEs. The study employed a quantitative explanatory research design using a survey approach. Data were collected from owners and managers of MSMEs through structured questionnaires distributed using proportional random sampling. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement model and test the proposed structural relationships among variables. The findings indicate that Accounting Information Systems have a positive and significant effect on the effectiveness of managerial decision-making by improving the availability, accuracy, relevance, and timeliness of financial information. Internal Control also demonstrates a significant positive influence by strengthening operational reliability, safeguarding organizational assets, ensuring regulatory compliance, and minimizing business risks that may affect managerial judgments. Furthermore, the simultaneous implementation of effective Accounting Information Systems and robust Internal Control contributes substantially to enhancing the quality of managerial decisions in MSMEs. These findings suggest that integrating digital accounting practices with comprehensive internal control mechanisms enables MSMEs to make more evidence-based, efficient, and strategic decisions. The study provides practical implications for MSME owners, policymakers, and business development institutions in designing strategies to strengthen financial management capabilities and improve organizational performance through technology adoption and sound governance practices.